2005
DOI: 10.1080/00071660500302661
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathology of gout in growing layers induced by high calcium and high protein diets

Abstract: 1. An experiment was conducted to test the independent and combined effects of high dietary calcium and protein concentrations on the induction of visceral gout in growing birds of a layer strain. 2. One hundred and sixty healthy birds were randomly divided into 4 groups at 35 d of age. The different groups were given 4 diets containing normal or high concentrations of dietary calcium or crude protein in a 2 x 2 factorial experiment for 30 d. The diets contained normal calcium (Ca) and crude protein (CP) (NCNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 11 publications
4
42
1
1
Order By: Relevance
“…Precipitation and crystallization of urates in the cases were probably favored by the electrolyte changes, disturbed tissue osmotic pressure, and the altered pH of the extracellular fluid (Mubarak and Sharkawy, 1999). Therefore, metabolic alkalosis found in the present study may partly explain why high dietary calcium in domestic birds could induce gout in our previous study (Guo et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Precipitation and crystallization of urates in the cases were probably favored by the electrolyte changes, disturbed tissue osmotic pressure, and the altered pH of the extracellular fluid (Mubarak and Sharkawy, 1999). Therefore, metabolic alkalosis found in the present study may partly explain why high dietary calcium in domestic birds could induce gout in our previous study (Guo et al, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…However, the beneficial effects of calcium can only be attained when the recommended doses are administered. Many metabolic problems, such as diuresis, urolithiasis, visceral gout, and poor pullet performance have been reported to be associated with excessive dietary calcium (Siller, 1981;Wideman and Cowen, 1987;Leeson and Summers, 1987;Wideman et al, 1993;Guo et al, 2005;Julian, 2005). Case histories of affected bird flocks often revealed that excessive calcium had been fed.…”
Section: Introductionmentioning
confidence: 96%
“…Nutritionally, visceral gout has been caused by water deprivation (9) and excesses of trace elements, e.g., zinc (23), and induced experimentally by highcalcium diets (24), high-calcium and high-protein diets (8), and hypovitaminosis A (7). Sodium bicarbonate, often supplemented to enhance egg-laying performance, caused visceral gout when administered experimentally to pullets in high doses (16).…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, elevated baseline UA levels indicate poor health and little ability to further increase levels because UA must be kept at concentrations low enough to avoid gout. That is, even if UA has beneficial effects as an antioxidant, high levels may indicate a compensatory response to stress, and there may be a ceiling on these levels imposed by the threat of gout (Guo et al 2005). Furthermore, although UA is a potent antioxidant, its physiological relevance is not well established.…”
Section: Uric Acid and Its Relation To Stressmentioning
confidence: 99%